2013
DOI: 10.1051/0004-6361/201321372
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre continuum observations of comet C/2009 P1 (Garradd)

Abstract: Context. Little is known about the physical properties of the nuclei of Oort Cloud comets. Measuring the thermal emission of a nucleus is one of the few means for deriving its size and constraining some of its thermal properties. Aims. We attempted to measure the nucleus size of the Oort Cloud comet C/2009 P1 (Garradd). Methods. We used the Plateau de Bure Interferometer to measure the millimetric thermal emission of this comet at 157 GHz (1.9 mm) and 266 GHz (1.1 mm). Results. Whereas the observations at 266 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A constant active area of approximately 75 km 2 can explain the water sublimation from the nucleus. As Garradd had a nucleus of radius <5.6 km (Boissier et al 2013) it must have had a very high active fraction (>20%). 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant active area of approximately 75 km 2 can explain the water sublimation from the nucleus. As Garradd had a nucleus of radius <5.6 km (Boissier et al 2013) it must have had a very high active fraction (>20%). 3.…”
Section: Discussionmentioning
confidence: 99%
“…Boissier et al (2013) found an upper limit of 5.6 km based on millimeter observations of the continuum emission from the nucleus, which suggest a continuous active surface fraction of >20%. This would be a significant part of Garradd's surface and much higher than the active areas deduced for most comets for which reliable size estimates exist.…”
Section: Water Production From the Nucleus And In The Comamentioning
confidence: 96%
“…In the sample of comets with D/H determinations (or significant upper limits), only eight comets have a known nucleus size, most of them from spacecraft images or radar measurements . We also consider the hyperactive comet C/2009 P1 (Garradd), whose nucleus effective radius has been constrained to be < 5.6 km (Boissier et al 2013). The effective nucleus radius of comet 46P/Wirtanen is estimated to 0.63 km from radar imaging.…”
Section: Correlation Between the D/h Ratio And Hyperactivitymentioning
confidence: 99%
“…As such, they have been the subject of extensive studies (we refer the reader to the comprehensive review by Levesque 2014), but no clear consensus has been reached in the community. Some investigations point toward a clear presence of a metallicity-dependence in the production of GRBs (e.g., Boissier et al 2013;Lunnan et al 2014), while others conclude that GRBs appear to be unbiased tracers of star formation (e.g., Fynbo et al 2008;Kohn et al 2015), and some highlight that discrimination between scenarios is challenging (e.g., Pontzen et al 2010;Laskar et al 2011).…”
Section: Introductionmentioning
confidence: 99%